2020
DOI: 10.1097/md.0000000000019091
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of IMP3 immunohistochemical expression in triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) account for 12% to 17% of all breast cancers. It is a heterogeneous group of tumors associated with aggressive clinical course. Insulin-like growth factor II mRNA binding protein 3 (IMP3) belongs to a family of insulin-like growth factor type II (IGF2), which plays a key role in the transmission and stabilization of mRNA, cell growth, and migration during embryogenesis. Increased expression of IMP3 is associated with aggressive behavior of different tumor types, advanced cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Growing evidence has demonstrated that m6A modification is closely associated with tumorigenesis, tumor differentiation, tumor proliferation, tumor invasion and worse survival in BC patients, including METTL3, METTL14, WTAP, ALKBH5, IGF2BP2, IGF2BP3, and FTO [3][4][5][6][7][8][9][10][11][12][13][14]. In addition, the m6A regulator IGF2BP3 was associated with reduced cell apoptosis, larger tumor sizes, higher grade, higher clinical stage, necrosis, and CK5/6 expression and further worsened the DFS and OS of BC patients [4,15,16]. However, the m6A regulator EIF3A had no association with age, tumor size, or differentiation grade.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has demonstrated that m6A modification is closely associated with tumorigenesis, tumor differentiation, tumor proliferation, tumor invasion and worse survival in BC patients, including METTL3, METTL14, WTAP, ALKBH5, IGF2BP2, IGF2BP3, and FTO [3][4][5][6][7][8][9][10][11][12][13][14]. In addition, the m6A regulator IGF2BP3 was associated with reduced cell apoptosis, larger tumor sizes, higher grade, higher clinical stage, necrosis, and CK5/6 expression and further worsened the DFS and OS of BC patients [4,15,16]. However, the m6A regulator EIF3A had no association with age, tumor size, or differentiation grade.…”
Section: Introductionmentioning
confidence: 99%
“…IMP3, as already mentioned, is a cytoplasmic marker found in many malignancies [1,2]. Since it shows a tendency towards higher expression in more aggressive neoplasms, it has been considered as a promising prognostic indicator [1][2][3][4][5][6]. However, while the number of studies suggesting the biological and clinical relevance of IMP3 is increasing, there is also a rising number of papers revealing apparent discrepancies with respect to the frequency of expression in some types of cancer [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is required for the migration of cells forming the roof plate of the neural tube which suggests that IMP3 may play an important role in promoting cell migration [1,2]. Moreover, IMP3 has gained considerable interest as a cancer-associated protein as it has been reported in a variety of human malignancies and has been linked to advanced disease stage and adverse clinical outcomes [1][2][3][4][5][6]. These data indicate that it may represent a valuable prognostic marker in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the studies in literature have reported IMP3 positivity in breast carcinoma ranging from 33 to 35.6% [ 16 18 ]. Contrary to this, in the present study, IMP3 immunopositivity was seen in 86.7% of the breast carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…IMP3 staining intensity also showed significant association with tumor histological grade ( p = 0.009) and TNM stage ( p = 0.036). Sjekloča et al also reported a significant association between IMP3 positivity and tumor size and TNM stage [ 18 ]. Similar to our study results, Walter et al also found a significantly higher expression of IMP3 in higher grade breast tumors ( p < 0.001) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%